Micronucleus assay on buccal cells: an indicator of DNA damage due to formaldehyde exposure in anatomy dissection labs - D Souza, Anne; Devi, Rema (International Journal of Research in Medical Sciences, 2017)
Background: The occupational exposure to formaldehyde (FA) can lead to various hazards ranging from allergic reactions to genetic damage. Workers of Anatomy lab are at a higher risk of having the hazardous effects of FA. Micronuclei (MN) appear in the cells due to chromosome breakage and dysfunction of the mitotic apparatus which are the indicators for the DNA damage. The present study was carried out to detect the DNA damage in people exposed to FA using buccal cell MN Assay by measuring the MN frequency in buccal cells with respect to the duration of exposure. Methods: Thirty male workers of Anatomy labs of different medial colleges in Bangalore were included in the study. Thirty people with no FA exposure were considered as comparison group. Buccal cells were scraped from the cheek and slides were prepared. A total of 1000 cells were counted for the presence of MN after staining with Geimsa solution. Results: There was a significant increase in the frequency of MN in both buccal cells (p<0.001). A positive correlation was found between the years of exposure and frequency of MN in buccal cells (r=0.5, p=0.03). Conclusion: This study highlights that there is a significant DNA damage in people exposed to formaldehyde which is proportional to the duration of exposure.